2022
DOI: 10.1111/1365-2656.13837
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune function and antioxidant capacity of nestlings of an African raptor covary with the level of urbanisation around breeding territories

Abstract: Urban areas provide breeding habitats for many species. However, animals raised in urban environments face challenges such as altered food availability and quality, pollution and pathogen assemblages. These challenges can affect physiological processes such as immune function and antioxidant defences which are important for fitness. Here, we explore how levels of urbanisation influence innate immune function, immune response to a mimicked bacterial infection and antioxidant capacity of nestling Black Sparrowha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…(2017) observed overrepresented genes involved in the secretion and receptor‐binding of cytokines in urban great tits ( Parus major ) compared to non‐urban tits. Additionally, urban nestling black sparrowhawks ( Accipiter melanoleucus ) had a stronger innate response to an immune challenge compared to non‐urban nestlings (Nwaogu et al., 2023). These studies provide evidence that urban living could confer an advantage against parasitism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) observed overrepresented genes involved in the secretion and receptor‐binding of cytokines in urban great tits ( Parus major ) compared to non‐urban tits. Additionally, urban nestling black sparrowhawks ( Accipiter melanoleucus ) had a stronger innate response to an immune challenge compared to non‐urban nestlings (Nwaogu et al., 2023). These studies provide evidence that urban living could confer an advantage against parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiles showed that urban nestlings differentially express innate immune genes associated with pro-inflammatory cytokines, specifically type-1 IFNs, compared to non-urban nestlings. When larval flies chew through the skin of their hosts, effective inflammation by the host (e.g., thickening the skin and restricting blood flow) can prevent ectoparasite feeding (reviewed in Owen et al, 2010) (Nwaogu et al, 2023). These studies provide evidence that urban living could confer an advantage against parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented in the literature that organisms inhabiting urban environments can face negative implications to their health and wellbeing [ 19 , 29 , 73 ]. Our results indicate that there is no significant effect of urbanization on overall avian health.…”
Section: Discussionmentioning
confidence: 99%
“…In two Australian passerines, coccidian infection increases with increasing urbanization in red-brown finches ( Neochima temporalis ), but not in superb fairy wrens ( Malurus cyaneus ) [ 28 ]. In black sparrowhawks ( Accipiter melanoleucus ), urbanization was negatively associated with some biomarkers of immunity and oxidative stress, while the majority of such markers were not affected [ 29 ]. Similarly, a large comparative analysis on the prevalence of Salmonella and Campylobacter in birds, two avian gastrointestinal bacteria, showed that while Salmonella prevalence was mostly affected by ecological factors including urbanization where prevalence was higher in urban areas, Campylobacter prevalence was largely associated with life-history traits [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Watson et al, (2017) observed overrepresented genes involved in the secretion and receptor-binding of cytokines in urban great tits ( Parus major ) compared to non-urban tits. Additionally, urban nestling black sparrowhawks ( Accipiter melanoleucus ) had a stronger innate response to an immune challenge compared to non-urban nestlings (Nwaogu et al, 2023). Although these studies were unable to link the heightened innate immune response in urban nestlings to parasite resistance, they provide evidence that urban living could confer an advantage against parasitism.…”
Section: Discussionmentioning
confidence: 99%